(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2012)
The efficiencies of Hexadecyltrimethylammonium bromide (HDTMABr) modified bentonite (HDTMABt) for phenol and chromium removal from aqueous solutions were studied in batch experiments at pH = 9 and pH = 2 values, respectively. FTIR, SEM, XRD and BET analyses indicated that the HDTMABr molecules were intercalated in the interlayer and at the external surface of initially Na-bentonite (NaBt). Adsorption experiments showed that the HDTMABt was more efficient than the initial NaBt for the removal of phenol and chromium, simultaneously, the extent of the enhancement differed among these pollutants depending on their affinity towards these samples. The kinetic study revealed a rapid adsorption onto HDTMABt of the pollutants during the initial stage (teq < 1h). The pseudo-second-order equation fitted well to the experimental data. Phenol adsorption on NaBt and HDTMABt could be described by a linear Freundlich equation while Langmuir and Freundlich models were the most suitable for Cr(VI) adsorption on both samples.Â